The Russian language norm in social perception - T. I. Sokolova (Вестник университета, 2022)
An important task of the language policy of the Russian Federation as a multinational state is to strengthen the unity and integrity of the country. In the context of multilingualism, the main unifying factor is the Russian language. Recently, there has been a decrease in the level of literacy of the population, a deviation from the language norms. The questions of standardisation and codification of language are not only the domain of linguistics. The language norm is a powerful tool of language policy, plays an important role in the formation, strengthening and development of national identity. The article presents an overview of the theoretical understanding of the language norm from the standpoint of scientific discourse and the legal framework. Based on the results of all-Russian sociological studies, the significance for the population of problems associated with raising the language culture level has been revealed. The purpose of the study is designated as revealing the status of the language norm in the legislative, linguistic and social aspects, determining the role of public perception of the language norm in strengthening the language policy of the Russian Federation. The main methods used were content analysis of normative documents and scientific literature, empirical analysis of secondary data from all-Russian sociological surveys, methods of generalization and interpretation. It has been found found that the citizens of Russia consider Russian language and language processes important, strive for the language literacy, and recognise the role of the state in regulating language policy and language norm-setting. It has been shown that the native speakers’ assessments can be used to strengthen the language policy in the Russian Federation, clarify its urgent tasks and their optimal solution.